ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KECAMATAN TANJUNG GADANG, KABUPATEN SIJUNJUNG - Robi Muhardi Putra; Armida Silvia; Menik Kurnia Siwi (Jurnal Ecogen, 2018)
This study aims to determine and analyze the influence of the amount of production (X1), land area (X2), the price of grain (X3), education (X4) and production costs (X5) on revenues of rice farmers in the district of Tanjung Gadang, Sijunjung . This type of research is descriptive and associative, wherein the data used are primary data in the form of Cross Section. In June 2018, the object of the research is rice farmers in the district of Tanjung Gadang, Sijunjung, with data collection techniques using direct observation, data collection tools using a questionnaire. The sampling method using Stage One cluster sampling method, the total sample in this study were 71 farmers of rice. Analysis of the data used is descriptive analysis and inductive analysis. In inductive analysis, there are several tests which are: (1) Linear Regression Model, (2) Prerequisites Test Analysis, (3) Test F and Test t. The results of this study show that (1) Total production of positive and significant impact on the income of rice farmers, means increasing the number of production will result in increased incomes of rice farmers in the district of Tanjung Gadang (2) The land area but not significant effect on the income of rice farmers, means increasing the land area then it will not have an impact on increasing the income of rice farmers in Tanjung Gadang  (3) Price grain positive and significant impact on the income of rice farmers, It means that the increase in grain prices will result in increased incomes of rice farmers in the district of Tanjung Gadang (4) The education level did not significantly affect the income of rice farmers, increasing educational means it will not have an impact on the decrease in income of rice farmers in the district of Tanjung Gadang (5) Cost of business no significant effect on the income of rice farmers, means increasing the cost of business then it will not have an impact on the decrease in income of rice farmers in the district of Tanjung Gadang, Simultaneously the amount of production, the land area, the price of grain, level of education and business costs affect the income of rice farmers in the district of Tanjung Gadang. Keyword: Rice Farmers' Income, Production, Land, Grain Prices and Education